ANALISIS PENGARUH MANAJEMEN PELATIHAN BERKELANJUTAN, ORGANIZATIONAL CULTURE DAN DIGITAL PERFORMANCE MANAGEMENT TERHADAP KINERJA KARYAWAN - Sri Purwati; Anugriaty Indah Asmarany; Muhamad Akbar; Amat Suroso; Mozart Malik Ibrahim; Marco Orias (POLITEKNIK LP3I JAKARTA, 2025)
Employee performance not only reflects individual effectiveness, but also contributes directly to the productivity and success of the organization as a whole. In Indonesia, the dynamics of the competitive labor market and technological developments require organizations to adopt innovative and adaptive human resource management strategies to ensure that employee performance remains optimal in the face of rapid change. This study uses a quantitative approach with confirmatory and explanatory strategies. The confirmatory strategy aims to test previously established hypotheses, while the explanatory strategy is used to explain the causal relationship between the variables studied. This approach is appropriate for identifying and analyzing the influence of continuous training management, organizational culture, and digital performance management on employee performance empirically. The results of this study clearly show that continuous training management, organizational culture, and digital performance management have a positive and significant influence on employee performance. The three variables are proven to provide substantial contributions in explaining variations in employee performance, with organizational culture acting as an important mediator in strengthening the influence of continuous training on individual performance in the workplace